The Effect of Self-Efficacy, Family Support, and Socio-Economic Factors on the Quality of Life of Patients with Breast Cancer at Dr Moewardi Hospital - Lusiatun -; Ambar Mudigdo; Bhisma Murti (Masters Program in Public Health, 2016)
Background:Breast cancer is the highest cancer among women in the world. Patients with breast cancer experience various changes, including physical, psychological and social changes. This changes affect their quality of life. This study aimed to determine the effect of self-efficacy, family support, and socio-economic factors on health-related quality of life of patients with breast cancer.Subjects and Method: This was an analytic observational study with cross sectional design. The study was conducted at Dr Moewardi Hospital, Surakarta. A total of 63 patients with breast cancer diagnosis were selected for this study by purposive sampling. The dependent variable was health-related quality life, consisting of global health status, physical function, role function, emotional function, social function, fatigue, pain, body image, financial hardship, and future perspective. The independent variables were self-efficacy, family support, education, and family income. The data were collected by questionnaire and medical record, and then were analyzed by multiple logistic regression.Results: Average age (and standard deviation) of the breast cancer patients under study was 50.21±7.67 years. Average score of quality of life in the global health status dimension was 73.81±10.97. Multiple logistic regression analysis showed positive effect of self-efficacy (OR=3.45;95% CI=0.98 to 12.12; p=0.053), family support (OR=2.67; 95%CI=0.84 to 8.46; p=0.096), education (OR=3.99; 95%CI=1.15 to 13.79; p=0.028), and family income (OR=1.51; 95%CI=0.43 to 5.26; p=0.518) on global health status.Conclusion:Self-efficacy, family support, education, and family income have positive and significant effects on global health status.Keywords: self-efficacy, family support, social economy, quality of life, breast cancerCorrespondence: Lusiatun. Masters of Public Health, Sebelas Maret University, Surakarta. Email: lusiatun12@gmail.com. Mobile: 085743778941Journal of Epidemiology and Public Health 2016, 1(3): 182-194https://doi.org/10.26911/jepublichealth.2016.01.03.05